Ergodicity of the mapping class group action on super-maximal representations - Maret, Arnaud (Arxiv, 2022)
This note investigates the dynamics of the mapping class group action on the character variety of super-maximal representations of the fundamental group of a punctured sphere into PSLp2, Rq, discovered by Deroin and Tholozan. We apply symplectic methods developed by Goldman and Xia to prove that the action is ergodic.